2006
DOI: 10.1007/s10874-006-1479-4
|View full text |Cite
|
Sign up to set email alerts
|

Water-Soluble dicarboxylic acids, ketoacids and dicarbonyls in the atmospheric aerosols over the southern ocean and western pacific ocean

Abstract: Water-soluble dicarboxylic acids (DCAs), ketoacids, and α-dicarbonyls in the marine aerosol samples collected over the Southern Ocean and western Pacific Ocean were determined. Oxalic acid was the most abundant species, followed by malonic acid and then succinic acid. It is suggested that aerosol concentrations of the organics over the Southern Ocean in this work represent their global background levels. Over the Southern Ocean, total concentrations of DCAs ranged from 2.9 to 7.2 ng m -3 (average: 4.5 ng m in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
68
3
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(81 citation statements)
references
References 46 publications
8
68
3
2
Order By: Relevance
“…The predominance of oxalic acid in Nainital aerosols is consistent with previous studies from urban, coastal marine and remote marine aerosols (Kawamura and Sakaguchi, 1999;Wang et al, 2006b), because this smallest diacid is a final product of the photochemical chain oxidations of aromatic hydrocarbons, isoprene, ethylene, and acetylene (Ervens et al, 2004) and may also be directly contributed from fossil fuel combustion (Kawamura and Kaplan, 1987) and biomass burning (Narukawa et al, 1999). During the winter period, oxalic acid concentrations were 393 ± 78 ng m −3 and 313 ± 88 ng m −3 for day and night, respectively.…”
Section: Concentrations Of Total Diacids Oversupporting
confidence: 91%
“…The predominance of oxalic acid in Nainital aerosols is consistent with previous studies from urban, coastal marine and remote marine aerosols (Kawamura and Sakaguchi, 1999;Wang et al, 2006b), because this smallest diacid is a final product of the photochemical chain oxidations of aromatic hydrocarbons, isoprene, ethylene, and acetylene (Ervens et al, 2004) and may also be directly contributed from fossil fuel combustion (Kawamura and Kaplan, 1987) and biomass burning (Narukawa et al, 1999). During the winter period, oxalic acid concentrations were 393 ± 78 ng m −3 and 313 ± 88 ng m −3 for day and night, respectively.…”
Section: Concentrations Of Total Diacids Oversupporting
confidence: 91%
“…Although LMW diacids can be emitted from primary sources such as vehicular exhausts (Kawamura and Kaplan, 1987), biomass burning (Legrand and de Angelis, 1996;Narukawa et al, 1999), cooking (Schauer et al, 2002) and natural marine sources (Rinaldi et al, 2011), they are mainly produced from the atmospheric photooxidation of various organic precursors (Kawamura and Gagosian, 1987;Stephanou, 1992;Kawamura and Sakaguchi, 1999) most likely in the aqueous aerosol phase (e.g., Sorooshian et al, 2006;Carlton et al, 2007;Ervens et al, 2008. LMW dicarboxylic acids and related compounds can contribute to 0.2-1.8 % of total carbon (TC) in urban Tokyo (Kawamura and Ikushima, 1993) and up to 16 % of TC in remote marine aerosols (Kawamura and Sakaguchi, 1999;Wang et al, 2006b).…”
Section: K Kawamura Et Al: Water-soluble Diacids Ketoacids and α-Dmentioning
confidence: 99%
“…This assumption is used because the CCN and water uptake properties of adipic acid (Table 1) have been widely studied (e.g. Bilde and Svenningsson, 2004;Broekhuizen et al, 2004;Corrigan and Novakov, 1999;Cruz and Pandis, 1997;Ervens et al, 2004;Hori et al, 2003;Joutsensaari et al, 2001;Prenni et al, 2001;Raymond and Pandis, 2002;Shulman et al, 1996) and adipic acid has been observed in the atmosphere (Grosjean et al, 1978;Kawamura and Yasui, 2005;Wang et al, 2006), and because some of its physico-chemical properties lie within a range of values from organic molecules.…”
Section: Simulations Of Organicsmentioning
confidence: 99%